Cell block technique as an additional tool in the diagnosis of ameloblastoma - Maria Fernanda da Silva BELATTO; Grasieli de Oliveira RAMOS; Manoela Domingues MARTINS; Liliane Janete GRANDO; Elena Riet Correa RIVERO (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The objective of this study was to evaluate the cytological content of ameloblastomas of the jaw. Nine cases of ameloblastoma were punctured, and the intralesional material was processed using the cell block technique. After centrifugation, the pellet obtained from the punctured material was fixed in formaldehyde and routinely processed to inclusion in paraffin. The obtained sections were stained with haematoxylin and eosin (H&E). Immunohistochemical reactions against anti-pan-cytokeratin (AE1/AE3) were performed to measure the presence of epithelial cells. Cytological analyses of the obtained slides revealed the presence of epithelial cells (as evidenced by AE1/AE3 labelling) and acellular amorphous eosinophilic materials. These cytological findings, in light of clinical and imaging data, can be helpful in the presumptive diagnosis of this disease entity by eliminating other possible diagnoses. Nonetheless further studies are needed in order to determine the nature of the acellular amorphous eosinophilic material and to ascertain the immunoprofile of epithelial cells.